Accounting Quality Indicators and Sustainable Shareholder Value Creation (gjstudies, 2025)
This research introduces a novel, cross-disciplinary framework that re-conceptualizesaccounting quality not merely as a compliance or transparency metric, but as a dynamic, multi-dimensional driver of sustainable shareholder value creation. Departingfrom traditional empirical finance and accounting studies that often treat accountingquality as a static, unidimensional construct, we propose a bio-inspired, adaptive systems model. This model, termed the Accounting Quality Ecosystem (AQE), analogizesfinancial reporting to a biological ecosystem where indicators such as earnings persistence, accrual quality, and disclosure timeliness interact in complex, non-linear waysto either nourish or deplete long-term corporate vitality. Our methodology synthesizesprinciples from complex adaptive systems theory, ecological resilience, and computational linguistics to construct a composite resilience index from conventional accounting signals. We apply this framework to a longitudinal dataset of firms, analyzinghow the configuration and interaction of quality indicators—rather than their isolatedlevels—predict resilience during economic shocks and capacity for value creation overextended horizons. The results demonstrate that specific synergistic configurationsof accounting quality indicators, which we label ’Symbiotic Quality Profiles,’ are robust predictors of sustainable excess returns and lower volatility of future earnings,even after controlling for known risk factors. These findings challenge the prevailingreductionist approach in the literature and offer a new paradigm for investors, regulators, and managers: that the holistic ’health’ of a firm’s information ecosystem,characterized by balanced and reinforcing quality traits, is a critical, yet previouslyunquantified, intangible asset. This research contributes original insights by bridgingecological concepts with financial reporting theory, providing a novel diagnostic toolfor assessing corporate longevity, and re-framing the pursuit of accounting quality asa strategic imperative for enduring shareholder value.